Contesting Inequality: The Impact of Immigrant Legal Status and Education on Legal Knowledge and Claims-Making in Low-Wage Labor Markets. (14th October 2020) - Patler, Caitlin; Gleeson, Shannon; Schonlau, Matthias
Abstract: Low-wage Latina/o workers are subject to an array of workplace abuses. This study focuses on whether educational attainment may moderate inequality in knowledge or claims-making across individuals with different legal statuses. This question is motivated by research which, while highlighting the role of education in promoting civic and political engagement, has not examined the interaction between education and legal status for worker claims-making. We draw from the 2008 Unregulated Work Survey, which is representative of the 1.64 million low-wage workers in Chicago, Los Angeles, and New York, three of the largest immigrant destinations in the United States. Using the Latina/o subsample, we test whether education impacts workers' procedural knowledge of the claims process, as well as their actual claims-making behavior, across four categories of workers: U.S.-born citizens, naturalized citizens, documented noncitizens, and undocumented noncitizens. Our findings reveal that all noncitizens have lower levels of procedural knowledge about how to file a complaint with the government, compared to citizens, across educational levels. However, when it comes to claims-making, we find that education has significant positive impacts for noncitizen workers, especially the undocumented. Our results suggest that education may improve the workplace agency of even the most marginalized workers.